2007
DOI: 10.1111/j.1754-4505.2007.tb00336.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of providing dental services to frail older adults: Perceptions of elders in adult day health centers*

Abstract: Very little is known about the oral health of, and access to, dental services among frail elders who live in the community and use an adult day health center (ADHC) for respite care. This pilot study evaluated the perceived oral health quality of life (OHQOL) of elders who used a mobile dental program in urban, suburban, and rural ADHC settings. Pre- and post-treatment interviews were conducted to evaluate OHQOL using the Geriatric Oral Health Assessment Index (GOHAI). ADHC records were used to obtain demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…In our recent study, however, comparable dental and prosthetic statuses and prevalence of dental treatment needs were observed among those with or without dementia, leading to similar OHRQoL. Similar levels of OHRQoL among demented and “healthy” elderly people have also been detected in previous studies 19,35…”
Section: Discussionsupporting
confidence: 80%
“…In our recent study, however, comparable dental and prosthetic statuses and prevalence of dental treatment needs were observed among those with or without dementia, leading to similar OHRQoL. Similar levels of OHRQoL among demented and “healthy” elderly people have also been detected in previous studies 19,35…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the importance of adequate daily oral care needs to be increasingly emphasized. Poor dental status may also result in reduced quality of life and difficulties in maintaining an active social life (Walker & Kiyak 2007). Thus, it seems that more dental health education needs to be included in nursing curricula (Wårdh et al 1997, Nicol et al 2005.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…Thus, perception of resistance is an important issue to overcome in dental hygiene education for nursing home staff. Furthermore, the importance of dental hygiene and its positive effects on general well-being need to be emphasized (Walker & Kiyak 2007).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Furthermore, literature studies have shown that the absence of teeth may have a negative influence on self-rated oral health [38][39][40], and that the elderly tend to improve in this area after rehabilitation [41][42][43][44].…”
Section: Psychosocial Dimensionmentioning
confidence: 99%